2020
DOI: 10.1039/d0cc01856b
|View full text |Cite
|
Sign up to set email alerts
|

Deep imaging for visualizing nitric oxide in lipid droplets: discovering the relationship between nitric oxide and resistance to cancer chemotherapy drugs

Abstract: A near-infrared two-photon fluorescent probe for selective detection and deep-depth imaging of NO helps to discover the relationship between NO and resistance to antitumor drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…One study demonstrated that DGAT1 in glioblastoma cells is capable of protecting tumors from lipotoxicity, labeling it as a potential metabolic target for cancer therapy [77]. Studies have also shown that the increase of nitric oxide (NO) levels in LDs can protect tumor cells and reduce the efficiency of chemotherapeutic drugs [78].…”
Section: Discussion: Understanding Ld Evolution May Provide Insight In How To Target Them In Paccsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study demonstrated that DGAT1 in glioblastoma cells is capable of protecting tumors from lipotoxicity, labeling it as a potential metabolic target for cancer therapy [77]. Studies have also shown that the increase of nitric oxide (NO) levels in LDs can protect tumor cells and reduce the efficiency of chemotherapeutic drugs [78].…”
Section: Discussion: Understanding Ld Evolution May Provide Insight In How To Target Them In Paccsmentioning
confidence: 99%
“…Varying studies have been focusing on utilizing NO inhibitors to effectively improve the effect of chemotherapeutic reagents [78]. Additional studies have shown that the chemotherapeutic agents, 5-fluorouracil, and oxaliplatin induce lysophosphatidylcholine acyltransferase 2 (LPCAT2) dependent LD accumulation [79].…”
Section: Discussion: Understanding Ld Evolution May Provide Insight In How To Target Them In Paccsmentioning
confidence: 99%
“…Currently, many probes have been developed for the imaging of intracellular active substances and/or single/double organelles. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] However, because of the p-p stacking and other non-radiative pathways, conventional fluorophores often suffer from an aggregation-caused quenching (ACQ) effect, which might lead to weak fluorescence emission in the aggregation state and easy photobleaching. Fortunately, a new class of aggregation-induced emission (AIE) luminogens that was first proposed by Tang' group in 2001, 30 could perfectly solve the ACQ problems.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the deep penetration of near-infrared excitation makes it a good tool for deep tissue imaging. 14 Recent studies have shown that the lysosomal membrane fuses with the autophagosome membrane during the autophagy process, which leads to an increase in its polarity. 15 Therefore, polarity-sensitive fluorescence probes with lysosomal targeting ability are becoming popular autophagy level assessment tools.…”
Section: Introductionmentioning
confidence: 99%